Evaluation of microelectrode materials for direct-current electrocorticography. (11th December 2015) - Li, Chunyan; Narayan, Raj K; Wu, Pei-Ming; Rajan, Neena; Wu, Zhizhen; Mehan, Neal; Golanov, Eugene V; Ahn, Chong H; Hartings, Jed A
Abstract: Objective . Direct-current electrocorticography (DC-ECoG) allows a more complete characterization of brain states and pathologies than traditional alternating-current recordings (AC-ECoG). However, reliable recording of DC signals is challenging because of electrode polarization-induced potential drift, particularly at low frequencies and for more conducting materials. Further challenges arise as electrode size decreases, since impedance is increased and the potential drift is augmented. While microelectrodes have been investigated for AC-ECoG recordings, little work has addressed microelectrode properties for DC-signal recording. In this paper, we investigated several common microelectrode materials used in biomedical application for DC-ECoG. Approach . Five of the most common materials including gold (Au), silver/silver chloride (Ag/AgCl), platinum (Pt), Iridium oxide (IrOx), and platinum-iridium oxide (Pt/IrOx) were investigated for electrode diameters of 300 μ m. The critical characteristics such as polarization impedance, AC current-induced polarization, long-term stability and low-frequency noise were studied in vitro (0.9% saline). The two most promising materials, Pt and Pt/lrOx were further investigated in vivo by recording waves of spreading depolarization, one of the most important applications for DC-ECoG in clinical and basic science research. Main results . Our experimental results indicate that IrOx-based microelectrodes, particularly with composite layers of nanostructures, are excellent in all of the common evaluation characteristics both in vitro and in vivo and are most suitable for multimodal monitoring applications. Pt electrodes suffer high current-induced polarization, but have acceptable long-term stability suitable for DC-ECoG. Major significance . The results of this study provide quantitative data on the electrical properties of microelectrodes with commonly-used materials and will be valuable for development of neural recordings inclusive of low frequencies.